2022
DOI: 10.3389/fpubh.2022.962083
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and quality of life in individuals with polycystic ovary syndrome: Dysmorphic concerns and eating disorders as mediators

Abstract: ObjectiveWeight issues, dysmorphic concerns and eating disorders are common among individuals with polycystic ovary syndrome (PCOS) and are linked to poor quality of life (QoL). The goal of the current study was to examine whether the association between body mass index (BMI) and QoL was mediated by dysmorphic concerns, examining also the relations with eating disorder symptomatology.MethodsQuestionnaires were administered to 435 individuals with PCOS aged between 18 and 40 years (M = 27.62; SD = 4.83) to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 107 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…5 Body image disturbance is a major factor in eating disorders, which can include irregular eating, restricted diets, and focus on body weight. 16 Excessive insulin and testosterone can spur an intense craving for carbs, signifying PCOS and BED 6 BED appears to be a factor in both obesity and disturbances in insulin regulation 7 Generally, fluctuating hormones during a menstrual cycle can influence food cravings and associated eating behavior 6 in PCOS women with ED. 30 Stress can cause a surge in appetite, resulting in overindulging and a higher Body Mass Index (BMI) in women with PCOS.…”
Section: Eating Disorder In Pcosmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Body image disturbance is a major factor in eating disorders, which can include irregular eating, restricted diets, and focus on body weight. 16 Excessive insulin and testosterone can spur an intense craving for carbs, signifying PCOS and BED 6 BED appears to be a factor in both obesity and disturbances in insulin regulation 7 Generally, fluctuating hormones during a menstrual cycle can influence food cravings and associated eating behavior 6 in PCOS women with ED. 30 Stress can cause a surge in appetite, resulting in overindulging and a higher Body Mass Index (BMI) in women with PCOS.…”
Section: Eating Disorder In Pcosmentioning
confidence: 99%
“…12 To sum it all up, severely heightened eating disorders can drastically reduce the quality of life to a very alarming degree. 16 The most common eating disorder observed in women with PCOS is BED 4 No AN-BP diagnosis was observed in PCOS individuals. 4 A meta-analysis investigation revealed that there was no statistical relationship between PCOS and AN-BP.…”
Section: Eating Disorder In Pcosmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 80% of PCOS women exhibit IR, which is independent of body mass index (BMI) and plays an important role in the clinical presentation and development of several metabolic alterations [7]. In adult women diagnosed with PCOS, BMI has been reported to correlate with poor quality of life (QoL), not only directly but also indirectly through the mediation of dysmorphic concerns [8]. Previous studies have shown that BMI is a predictor of body dissatisfaction in young adolescent girls [9].…”
Section: Introductionmentioning
confidence: 99%